Antitumor effect of exopolysaccharide produced by Bacillus mycoides. (March 2020) - Farag, Mohamed M.S.; Moghannem, Saad A.M.; Shehabeldine, Amr M.; Azab, Mohamed S.
Abstract: Recently, microbial exopolysaccharides (EPSs) have offered very large field for medical applications owing to their bioactive characteristics. This study aimed to obtain antitumor EPS and to optimize its production using different optimization approaches. Eighty EPSs-producing bacteria were obtained from mud samples. Isolate BS4 was selected as the most potent antitumor EPS-producer and identified as Bacillus mycoides BS4 using 16S rRNA gene sequence analysis. Cell viability and antitumor activity of produced EPS were investigated using microscopic examination and MTT assay. Interestingly, the produced EPS exhibited low cytotoxicity against normal cell baby hamster kidney (BHK) with IC50 at 254 μgml −1 while it exhibited an inhibitory effect against cancer cells of human hepatocellular carcinoma (HepG2) and Colorectal adenocarcinoma cells (Caco-2) with IC50 of 138 μgml −1 and 159 μgml −1, respectively. The purified EPS was characterized using Fourier transform infrared, gel permeation chromatography and gas chromatography–mass spectroscopy. It showed molecular weight of 1.90 × 10 4 Da and consists of galactose, mannose, glucose and glucuronic acid. The factors affecting EPS production were optimized using one-factor-at-a time and statistical optimization methods. The Placket-Burman (PB) design results indicated that sugarcane molasses, peptone and shaking conditions were the most significant variables, which were further optimized by Response Surface Methodology (RSM). The optimum conditions for EPS production were 8.0% ( w/v ) sugarcane molasses, 6 gL ‒1 peptone and 300 rpm that produce 8.02gL ‒1 of EPS. This indicates the potentiality of Bacillus mycoides BS4 for production of EPS with biomedical applications. Highlights: Cancer is one of the most malignant diseases threatening human and cause mortality worldwide. Microbial exopolysaccharides offers very large field for medical applications owing to their bioactive characteristics. Potentiality of Bacillus mycoides for production of EPS with biomedical applications. Biological production of EPSs offers several advantages compared to chemical production methods.